Flexible lead-free X-ray protective coating fabric and preparation method thereof
The preparation of bismuth oxide-silicon rubber-based flexible lead-free X-ray protection coating fabric was solved by coating method, which solved the problems of toxicity, bulkiness and poor elasticity of existing lead-containing protective materials, and achieved efficient X-ray protection effects that are lead-free, lightweight, non-toxic and soft.
Patent Information
- Application Number
- CN202510181738.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing lead-containing X-ray radiation protection materials have problems such as toxicity, bulkiness and poor elasticity, and it is difficult to meet the needs of lead-free, lightweight, non-toxic and flexible.
The bismuth oxide-silica rubber-based flexible lead-free X-ray protective coating fabric was prepared by coating method. By mixing bismuth oxide powder with silicone rubber and ethyl acetate, mechanically stirring, evenly applying it to the surface of the polyester fabric, and vulcanizing and shaping at high temperature.
A lead-free, non-toxic, light and soft X-ray protection material is achieved. When the bismuth oxide content in every 100g of silicone rubber is 240g, the protective material has the best rigidity and flexibility, and the X-ray protection ratio per unit volume reaches 29.73%, which is significantly lower than the density of conventional lead-containing protective materials.
Smart Images

Figure CN119877294A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coated fabrics, and in particular to a flexible lead-free X-ray protective coated fabric and a preparation method thereof. Background Art
[0002] As a short-wave ionizing radiation source, X-rays are widely used in defense and military industry, industrial flaw detection, medical diagnosis and treatment, archaeology and other fields. Excessive exposure to high-energy rays may seriously damage human health, and its effects range from mild symptoms (rashes, skin burns, nausea and headaches) to fatal diseases (cancer and gene mutations), which may lead to permanent disability or death. In order to reduce or prevent this risk, it is necessary to vigorously develop radiation protection materials. Radiation shielding is a very effective way to protect against ionizing radiation, especially when distance and time are limited. However, most of the most common radiation shielding materials on the market contain lead (Pb), which is toxic and can cause health hazards. Moreover, lead-containing radiation shielding materials are bulky and have poor elasticity, which greatly limits their use in radiation protection applications. Therefore, it is very necessary to develop lead-free, lightweight, non-toxic and flexible X-ray radiation shielding materials. Summary of the invention
[0003] The purpose of the present invention is to disclose a flexible lead-free X-ray protective coating fabric and a preparation method thereof. The bismuth oxide-silicone rubber-based flexible lead-free X-ray protective coating fabric is prepared by a coating method. The fabric is lead-free, non-toxic, light and soft. In addition, when the bismuth oxide content in every 100g of silicone rubber is 240g, the rigidity and flexibility of the protective material are optimal; the density of the flexible protective material with different bismuth oxide contents is 0.8-1.6g·cm -3 , significantly lower than conventional lead-containing protective materials; considering the X-ray protection performance and softness of bismuth oxide-silicone rubber-based lead-free X-ray flexible protective fabric, 240g of bismuth oxide per 100g of silicone rubber is the optimal solution, and the X-ray protection ratio per unit volume of polyester fabric reaches 29.73%.
[0004] To achieve the above object, the present invention provides a method for preparing a flexible lead-free X-ray protective coating fabric, comprising the following steps:
[0005] (1) Preparation of a flowing colloidal coating liquid: bismuth oxide powder is mixed with transparent liquid silicone rubber A, transparent liquid silicone rubber B and ethyl acetate in a certain proportion, and mechanically stirred to obtain a flowing colloidal coating liquid;
[0006] (2) Pretreatment of polyester fabric: Pre-dry the polyester fabric in an oven at 160℃-170℃ for 2-3 minutes;
[0007] (3) Scraping process: Apply the flowing colloid coating liquid evenly on the surface of the polyester fabric;
[0008] (4) High temperature vulcanization and shaping: After coating the polyester fabric once, place the polyester fabric in a 160℃-200℃ oven and bake for 2-3 minutes to quickly solidify the coating. Repeat the above operation until both sides of the polyester fabric are coated several times to obtain a flexible lead-free X-ray protective coating fabric.
[0009] In some embodiments, in the flowing colloid coating liquid, per 100 g of transparent liquid silicone rubber B, the content of bismuth oxide is 0-480 g, the content of ethyl acetate is 10-240 g, and the content of transparent liquid silicone rubber A is 2 g.
[0010] In some embodiments, in the flowing colloid coating liquid, per 100 g of transparent liquid silicone rubber B, the content of bismuth oxide is 240 g, the content of ethyl acetate is 120 g, and the content of transparent liquid silicone rubber A is 2 g.
[0011] In some embodiments, the transparent liquid silicone rubber A is a curing agent, and the curing agent is a platinum vulcanizing agent.
[0012] In some embodiments, during the preparation of the flowing colloidal coating liquid, the mechanical stirring time is 30 min.
[0013] In some embodiments, in the scraping process, first, the polyester fabric is gently patted with a brush, and the polyester fabric is fixed on a rectangular sample frame under a certain tension. Then, a scraper is used to scrape the flowing colloid coating liquid evenly on the surface of the polyester fabric at 45 degrees.
[0014] In some embodiments, during high-temperature vulcanization and shaping, after the surface of the polyester fabric is coated with one knife, the polyester fabric on the sample frame is placed in a 160°C-200°C oven and baked for 2-3 minutes to allow the coating to quickly solidify and shape, that is, the first knife coating is completed, and the above operation is repeated until the front and back sides of the polyester fabric are both coated with two knives to obtain a flexible lead-free X-ray protective coating fabric.
[0015] To achieve the above object, the present invention also provides a flexible lead-free X-ray protective coating fabric, which is prepared by the above-mentioned preparation method of the flexible lead-free X-ray protective coating fabric.
[0016] In some embodiments, the X-ray protection ratio per unit volume of the coated fabric is 29.73%.
[0017] Compared with the prior art, the invention has the following beneficial effects: the bismuth oxide-silicone rubber-based flexible lead-free X-ray protective coating fabric is prepared by a coating method, which is lead-free, non-toxic, light and soft. In addition, when the bismuth oxide content in every 100g of silicone rubber is 240g, the rigidity and flexibility of the protective material are optimal; the density of the flexible protective material with different bismuth oxide contents is 0.8-1.6g·cm -3, significantly lower than conventional lead-containing protective materials; considering the X-ray protection performance and softness of bismuth oxide-silicone rubber-based lead-free X-ray flexible protective fabric, 240g of bismuth oxide per 100g of silicone rubber is the optimal solution, and the X-ray protection ratio per unit volume of polyester fabric reaches 29.73%. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The present invention is a process flow chart of the preparation of a flexible lead-free X-ray protective coating fabric;
[0019] Figure 2 The formula of the flowing colloid coating liquid in the present invention;
[0020] Figure 3 is a curve diagram showing the variation of the surface density of the sample with the bismuth oxide content;
[0021] Figure 4 is a curve diagram showing the variation of sample thickness with bismuth oxide content;
[0022] Figure 5 is a curve diagram showing the change of density of the sample with the bismuth oxide content;
[0023] Figure 6 Schematic diagram of measuring fabric rigidity and flexibility using the inclined plane method;
[0024] Figure 7 is a curve diagram showing the variation of the flexural stiffness and flexural elastic modulus of the sample with the bismuth oxide content;
[0025] Figure 8 This is a curve chart showing the change in X-ray protection ratio of the sample with the bismuth oxide content. DETAILED DESCRIPTION
[0026] The present invention is described in detail below in conjunction with the various embodiments shown in the accompanying drawings, but it should be noted that these embodiments are not limitations of the present invention, and any equivalent transformations or substitutions in functions, methods, or structures made by ordinary technicians in the field based on these embodiments are all within the scope of protection of the present invention.
[0027] This embodiment discloses a method for preparing a flexible lead-free X-ray protective coating fabric and a flexible lead-free X-ray protective coating fabric prepared by the method. The preparation process flow chart is shown in FIG. Figure 1 As shown, the specific steps include:
[0028] (1) Preparation of flowing colloidal coating liquid: bismuth oxide powder was mixed with transparent liquid silicone rubber A, transparent liquid silicone rubber B and ethyl acetate in a certain proportion, and mechanically stirred for 30 minutes to obtain a flowing colloidal coating liquid.
[0029] like Figure 2The specific formula of the flowing colloid coating liquid shown is that the transparent liquid silicone rubber B is a constant. In this patent, the transparent liquid silicone rubber B is referred to as silicone rubber. The amount of bismuth oxide and ethyl acetate is calculated based on 100g of transparent liquid silicone rubber B; the filling amount of bismuth oxide in 100g of transparent liquid silicone rubber B is 0g to 480g, increasing by 60g; the amount of ethyl acetate is 0.5 times the amount of bismuth oxide; transparent liquid silicone rubber A is the curing agent (platinum vulcanizer), and its amount is calculated based on the mass ratio of transparent liquid silicone rubber B, and the mass of the curing agent in 100g of transparent liquid silicone rubber B is 2g.
[0030] Bismuth is a green, non-toxic metal element with a greater attenuation coefficient than lead, stable chemical properties, and strong X-ray absorption. Bismuth oxide (Bi2O3) is considered an ideal substitute for lead. In addition, relevant studies have shown that micro-nano fillers have excellent protection against radiation. Silicone rubber has the characteristics of small elastic modulus, high elongation, high air tightness, corrosion resistance, and high load-bearing capacity. It is one of the good materials for making isolation protective clothing. In addition, the silicone rubber coating technology is relatively mature and the process is relatively simple, which is accepted by most companies.
[0031] (2) Pretreatment of polyester fabric: In order to make the surface tension of polyester fabric uniform and the hairiness smooth, and to minimize the small bubbles caused by the rapid heating of the flowing colloid on the surface of the fabric, the polyester fabric was pre-dried in an oven at 165℃ for 3 minutes before coating;
[0032] (3) Scraping process: First, gently pat the polyester fabric with a brush, fix the polyester fabric on a rectangular sample frame under a certain tension, and then use a scraper at 45° to evenly scrape the flowing colloid coating liquid on the surface of the polyester fabric.
[0033] (4) High temperature vulcanization and shaping: After the polyester fabric surface is coated with one scrape, the polyester fabric on the sample frame is placed in a 170°C oven and baked for 2 minutes to allow the coating to quickly solidify and shape. This means that the first scrape is completed. Repeat the above operation until the front and back sides of the polyester fabric are both coated with two scrapes to obtain a flexible lead-free X-ray protective coating fabric.
[0034] According to Figure 2 The specific formula of the flowing colloid coating liquid shown was used to produce 9 flexible lead-free X-ray protective coating fabric samples, and their density, rigidity, flexibility, and X-ray protective performance were tested and compared to obtain the best formula of the flowing colloid coating liquid. The specific test analysis is as follows:
[0035] 1. Effect of bismuth oxide content on sample density
[0036] Surface density test method: Refer to GB / T4669-2008 "Determination of mass per unit length and mass per unit area of textile woven fabrics" to cut the sample into 20cm*13cm (length × width) size, weigh its mass, and calculate the surface density. Each group of samples is measured 3 times and the average value is taken. Since there may be colloid accumulation at both ends of the sample, the middle part of the sample should be taken for testing.
[0037] Thickness test method: Refer to ISO 2808-2019 "Determination of film thickness of paints and varnishes", use a digital fabric thickness gauge to measure the sample thickness along the diagonal. Set test parameters: presser foot area 50mm 2 , the pressing weight is 100cN, the pressing time is 10s, the pressing foot descending speed is 1.72mm / s, and the test is continuous. Each group of samples is measured 7 times and the average value is taken.
[0038] Figure 3 The surface density of the sample changes with the bismuth oxide content. The results show that the surface density of the sample increases with the increase of bismuth oxide content. When the bismuth oxide content reaches 360g, the surface density of the sample is the largest, reaching 474g / m 2 , and then the bismuth oxide filling amount is increased, and its surface density decreases slightly and tends to be flat. This is because the ratio of bismuth oxide to silicone rubber determines the contact probability between the two on the one hand, and also determines the distribution state of bismuth oxide in silicone rubber. When the bismuth oxide content is low (<360g), the bismuth oxide powder is gradually distributed in the continuous phase liquid silicone rubber; with the increase of bismuth oxide content (≥360g), in addition to contacting with silicone rubber, the bismuth oxide powder will also form self-aggregated particles, thereby reducing the fluidity of bismuth oxide powder in liquid silicone rubber, affecting its dispersion state in silicone rubber, and causing more powder and less glue on the surface of the sample. For this reason, when the bismuth oxide content exceeds 360g, the polyester fabric will drop a large amount of powder after drying, which will eventually cause its surface density to decrease slightly and tend to be flat.
[0039] Figure 4 The graph of the thickness of the sample changes with the bismuth oxide content. It can be seen that due to the presence of the coating, the thickness of the sample is greater than that of the uncoated polyester fabric. As the bismuth oxide content increases, the thickness of the sample increases first and then decreases. When the bismuth oxide content reaches 240g, the sample thickness is the largest, which is 0.39mm. After that, it shows a downward trend with the increase of the bismuth oxide content. The reason is that before the bismuth oxide content reaches 240g, the dispersion state of bismuth oxide powder in silicone rubber is better, and the thickness of the sample mainly depends on the amount of glue. As the bismuth oxide content continues to increase, the dispersion state of bismuth oxide in silicone rubber gradually deteriorates, causing the powder on the coating surface to fall off. Therefore, the thickness of the sample will show a trend of first fluctuating increase, then fluctuating decrease, and finally tending to be flat.
[0040] The density of the sample is calculated based on the thickness and surface density of the sample. Figure 5 The density of the sample changes with the bismuth oxide content. The density of the sample increases with the increase of bismuth oxide content. The density is between 0.8 and 1.6 g cm -3 In addition, when the bismuth oxide content reaches 480g, the proportion of bismuth oxide powder is too large, and its dispersion state in silicone rubber deteriorates, resulting in powder shedding, which leads to a low measured sample density. The unit area weight (gram weight) of conventional commercial lead-containing protective materials is about 2.5kg·m -2 , the thickness is about 0.66mm, and its density is 3.79g·cm -3 .
[0041] Therefore, the density of the flexible lead-free X-ray protective coating fabric prepared in this embodiment is significantly lower than that of conventional lead-containing protective materials. Under the same volume, the flexible lead-free X-ray protective coating fabric is lighter.
[0042] 2. Effect of bismuth oxide content on sample rigidity and flexibility
[0043] Rigidity and flexibility test method: Refer to GB / T183181-2009 "Determination of flexural properties of textiles Part 1: Inclined plane method" to test the rigidity and flexibility of the sample. See the test diagram for details. Figure 6 The angle θ of the trapezoidal table is 41.5°, and the calculation formula is shown in equations (1)-(3). The sample size is 20cm*2cm (length×width), and each group of samples is tested 6 times to take the average value.
[0044] C=0.5·L (1)
[0045] B=9.8·G·C 3 ×10 -5 (2)
[0046]
[0047] Where: C is the bending length, cm; L is the sliding length, cm; B is the bending stiffness, cN / cm; G is the surface density, g / m 2 ; q is the bending elastic modulus, N / cm 2 ; t is the sample thickness, mm.
[0048] From equations (1)-(3), it can be seen that the bending elastic modulus q is affected by the surface density G, bending length C, and thickness t. The smaller the q value, the better the bending performance and the softer the sample. Figure 7The following is a curve of the bending stiffness and bending elastic modulus of the sample with the bismuth oxide content. The results show that the bending elastic modulus of the samples with bismuth oxide content of 60-480g is greater than that of the uncoated polyester fabric, indicating that the bending performance of the coated fabric is worse than that of the uncoated polyester fabric, and the fabric becomes harder after coating. As the bismuth oxide content increases, the bending elastic modulus generally shows a trend of first increasing and then fluctuating and decreasing. The reason is that when the bismuth oxide content is ≤180g, the bismuth oxide powder is evenly distributed in the silicone rubber and gradually increases, which increases the surface density G, the bending length C, and finally the bending stiffness B. The thickness t is slightly reduced, so q becomes larger and the softness of the sample becomes worse.
[0049] When the bismuth oxide content reaches 240 g, the bending stiffness of the sample changes less than that of the fabric with a low bismuth oxide content, while its thickness reaches a maximum value such as Figure 4 As shown in the figure, its flexural modulus is greatly reduced. Therefore, when the bismuth oxide content reaches 240g, the sample has the best softness.
[0050] When the bismuth oxide content is greater than 240g, the bending stiffness B mainly depends on the bending length C, and the sliding length L is reduced relative to the 180g bismuth oxide filling amount, which makes the bending length C smaller, so its bending stiffness B is reduced. At the same time, due to the high bismuth oxide content, the volume of bismuth oxide powder is greater than the volume of silicone rubber, and the fabric thickness t is reduced, so its bending elastic modulus q shows a downward trend, and the softness of the sample gradually improves.
[0051] 3. Analysis of the effect of bismuth oxide content on the X-ray protection performance of samples
[0052] X-ray protection performance test method: refer to GBZ / T 147-2002 "Determination of attenuation performance of radiation protection materials", use the X-ray air kerma (protection level) standard device to test the X-ray protection performance of bismuth oxide-silicone rubber-based flexible protection materials. The sample thickness is less than 0.5mm, and the incident energy is set to 48keV. The calculation method of X-ray protection ratio is shown in formula (4).
[0053]
[0054] Where: η is the X-ray protection ratio, %; I0 is the initial incident X-ray dose rate, μGy; I is the X-ray dose rate passing through the protective material, μGy.
[0055] Figure 8The graph of the X-ray protection ratio of the sample changes with the bismuth oxide content. It can be seen that the X-ray protection ratio of the sample shows a trend of first rising and then falling with the increase of the bismuth oxide content. When the bismuth oxide content is 240g and 300g, the X-ray protection ratio of the sample is about 19%; when the bismuth oxide content reaches 360g, the X-ray protection ratio of the sample is the highest, which is 28.81%; and then with the increase of the bismuth oxide content, the X-ray protection ratio of the sample decreases and tends to be flat. The reason is that when the bismuth oxide content is higher than 360g, with the increase of bismuth oxide content, agglomerated particles and powder-coated glue appear in the surface coating of the polyester fabric, resulting in a decrease in the X-ray protection performance of the polyester fabric.
[0056] In addition, since the thickness of the coated polyester fabric changes with the bismuth oxide content, the effect of bismuth oxide content on the X-ray protection performance per unit volume of polyester fabric was studied by comparing and analyzing the protection ratio per unit volume of polyester fabrics with different bismuth oxide contents. Figure 8 It can be seen that the X-ray protection ratio per unit volume of samples with different bismuth oxide contents shows an overall trend of first increasing and then decreasing with the increase of bismuth oxide content. When the bismuth oxide content is 240g, the X-ray protection ratio of polyester fabric is the highest, which is 29.73%, which is close to the X-ray shielding efficiency (31.9%) of the nanocomposite material prepared by Motakegf Kazemi et al. with polymethyl methacrylate (PMMA) as the polymer matrix and bismuth oxide nanoparticles as filler. At this time, the ratio of bismuth oxide powder and silicone rubber reaches the optimal level, and the dispersion uniformity of bismuth oxide in silicone rubber is relatively good.
[0057] When the bismuth oxide content increases from 60g to 180g, as the bismuth oxide powder content increases, the bismuth element content in the coating gradually increases and the dispersion becomes more uniform and denser, and the X-ray protection ratio per unit volume gradually increases; when the bismuth oxide content is equal to or higher than 300g, the X-ray protection ratio per unit volume of the polyester fabric is not much different from that of 360g, because at this time the bismuth oxide powder content exceeds the limit that the colloid can accommodate, resulting in the agglomeration of bismuth oxide particles on the coating surface and easy to fall off. In addition, the softness of the polyester fabric with a bismuth oxide content of 300g is far inferior to the performance of the polyester fabric with a bismuth oxide content of 240g. Comprehensively compared, the polyester fabric with a bismuth oxide content of 240g per 100g of silicone rubber (i.e., SR / Bi2O3100 / 240) has the best X-ray protection performance and softness.
[0058] Bismuth oxide-silicone rubber-based flexible lead-free X-ray protective coating fabric was prepared by coating method. It is lead-free, non-toxic, light and soft. In addition, when the bismuth oxide content in every 100g of silicone rubber is 240g, the rigidity and flexibility of the protective material are optimal; the density of the flexible protective material with different bismuth oxide contents is 0.8-1.6g·cm -3, significantly lower than conventional lead-containing protective materials (3.79 g·cm -3 ); Taking into account the X-ray protection performance and softness of the bismuth oxide-silicone rubber-based lead-free X-ray flexible protective fabric, 240g of bismuth oxide per 100g of silicone rubber is the optimal solution, and the X-ray protection ratio per unit volume of polyester fabric reaches 29.73%.
[0059] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present invention. They are not intended to limit the scope of protection of the present invention. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
[0060] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a flexible lead-free X-ray protective coating fabric, characterized in that: The steps include: (1) Preparation of a flowing colloidal coating liquid: bismuth oxide powder is mixed with transparent liquid silicone rubber A, transparent liquid silicone rubber B and ethyl acetate in a certain proportion, and mechanically stirred to obtain a flowing colloidal coating liquid; (2) Pretreatment of polyester fabric: Pre-dry the polyester fabric in an oven at 160℃-170℃ for 2-3 minutes; (3) Scraping process: Apply the flowing colloid coating liquid evenly on the surface of the polyester fabric; (4) High temperature vulcanization and shaping: After coating the polyester fabric once, place the polyester fabric in a 160℃-200℃ oven and bake for 2-3 minutes to quickly solidify the coating. Repeat the above operation until both sides of the polyester fabric are coated several times to obtain a flexible lead-free X-ray protective coating fabric.
2. The method for preparing the flexible lead-free X-ray protective coating fabric according to claim 1, characterized in that: In the flowing colloid coating liquid, per 100g of transparent liquid silicone rubber B, the content of bismuth oxide is 0-480g, the content of ethyl acetate is 10-240g, and the content of transparent liquid silicone rubber A is 2g.
3. The method for preparing the flexible lead-free X-ray protective coating fabric according to claim 2, characterized in that: In the flowing colloid coating liquid, per 100 g of transparent liquid silicone rubber B, the content of bismuth oxide is 240 g, the content of ethyl acetate is 120 g, and the content of transparent liquid silicone rubber A is 2 g.
4. The method for preparing the flexible lead-free X-ray protective coating fabric according to claim 2 or 3, characterized in that: The transparent liquid silicone rubber A is a curing agent, and the curing agent is a platinum vulcanizing agent.
5. The method for preparing the flexible lead-free X-ray protective coating fabric according to claim 1, characterized in that: In the preparation of the flowing colloid coating liquid, the mechanical stirring time is 30 minutes.
6. The method for preparing the flexible lead-free X-ray protective coating fabric according to claim 5, characterized in that: In the scraping process, first, the polyester fabric is gently patted with a brush, and the polyester fabric is fixed on a rectangular sample frame under a certain tension. Then, a scraper is used to scrape the flowing colloid coating liquid evenly on the surface of the polyester fabric at 45 degrees.
7. The method for preparing the flexible lead-free X-ray protective coating fabric according to claim 6, characterized in that: During the high-temperature vulcanization and shaping, after the polyester fabric surface is coated with one knife, the polyester fabric on the sample frame is placed in a 160℃-200℃ oven and baked for 2-3 minutes to allow the coating to quickly solidify and shape, that is, the first knife coating is completed. Repeat the above operation until the front and back sides of the polyester fabric are both coated with two knives to obtain a flexible lead-free X-ray protective coating fabric.
8. A flexible lead-free X-ray protective coating fabric, characterized in that: The flexible lead-free X-ray protective coating fabric is prepared by the preparation method of any one of claims 1 to 7.
9. The flexible lead-free X-ray protective coating fabric according to claim 8, characterized in that: The X-ray protection ratio per unit volume of the coated fabric is 29.73%.
Citation Information
Patent Citations
Flexible lead-free X-ray protection material as well as preparation method and application thereof
CN113929356A
Cited By
Micro-gear-shaped special-shaped stretchable conductive anti-radiation fiber as well as preparation and application thereof
CN120649194A
A micro-gear-shaped special-shaped stretchable conductive radiation-proof fiber and its preparation and application
CN120649194B